A nitrogen-doped carbon dot and its preparation method and application
By preparing nitrogen-doped carbon dots containing carboxyl carbon sources and 5-12 N-containing heterocyclic compounds, the problem of insufficient shielding performance of existing carbon dot materials in the full ultraviolet band has been solved, and the high efficiency of ultraviolet absorption and aging resistance has been improved, making them suitable for polymer films and sunshade products.
Patent Information
- Application Number
- CN202211284964.4
- Authority / Receiving Office
- CN · China
- Patent Type
- Patents(China)
- Current Assignee / Owner
- Filing Date
- 2022-10-20
- Publication Date
- 2025-01-10
- Estimated Expiration
- 2042-10-20
AI Technical Summary
Existing carbon dot materials have poor shielding performance in the full ultraviolet band and insufficient resistance to aging and acids and alkalis, which cannot meet the long-term use requirements of outdoor protective materials.
Using carboxyl-containing carbon sources and 5-12 N-containing heterocyclic compounds as nitrogen sources, nitrogen-doped carbon dots are prepared through hydrothermal reaction to form carbon dots with excellent ultraviolet absorption characteristics, thereby enhancing their absorption performance in the entire ultraviolet band and maintaining high transmittance in the 400-800 nm range.
The prepared nitrogen-doped carbon dots have an absorption efficiency of over 99% in the entire ultraviolet band and excellent transmittance in the visible light region. They also have excellent resistance to photoaging and acid resistance, making them suitable for preparing polymer films and sunshade products.
Smart Images

Figure BDA0003899401470000031 
Figure FDA0005136401860000011 
Figure HDA0003899401480000011
Abstract
Description
Technical Field
[0001] The present invention belongs to the technical field of carbon materials, and in particular relates to nitrogen-doped carbon dots and a preparation method and application thereof. Background Art
[0002] Ultraviolet rays are part of sunlight, including UV-C (200-280nm), UV-B (280-320nm) and UV-A (320-400nm). Among them, UV-C cannot pass through the ozone layer to reach the earth's surface. Although the intensity of UV-B and UV-A radiation is much lower than that of visible light and infrared radiation, the energy of their photons exceeds the energy of carbon-carbon single bonds. When ultraviolet radiation combines with oxygen in the air, it can cause free radicals in polymer materials, eventually leading to the degradation of polymer materials. Without protection, long-term exposure of human skin to sunlight can also lead to various harmful effects. Among them, UV-B, as the main active band on the earth, can cause chronic effects such as erythema, skin burns, skin photoaging and immunosuppression at the mildest, and direct photochemical damage to human DNA at the worst, causing gene mutations, and is one of the main factors in the development of skin cancer. UV-A can induce skin tanning, and long-term exposure can cause skin damage, loss of skin elasticity, wrinkles, and induce phototoxicity and photoallergic reactions.
[0003] With global climate change in recent decades, the ozone layer has experienced long-term depletion, its composition has been changing, its thickness has become thinner, and the dose of ultraviolet radiation has increased accordingly. Combined with the rising incidence of skin cancer reported worldwide in recent years, the public's demand for various sunscreen products has greatly increased. Such as wearing sunglasses, holding parasols, wearing clothing with sunscreen functions, using cosmetics with sunscreen formulas, etc. At the same time, with the continuous upgrading of industrial machines and medical equipment, the demand for solid transparent materials that can provide high ultraviolet shielding efficiency has increased, such as sunshade ceilings, UV-proof contact lenses, special protective packaging materials, etc. These materials can be manufactured by incorporating suitable ultraviolet absorbing materials into transparent polymer matrices. Although both organic ultraviolet absorbers and inorganic ultraviolet absorbers (such as TiO2, ZnO, etc.) can be used as ultraviolet shielding materials, their transparency is low and they cannot complete full-band ultraviolet shielding. The acid and alkali resistance, stability and weather resistance are not enough for long-term use. Therefore, it is necessary to develop new ultraviolet shielding materials with high stability, high transparency and full-band ultraviolet shielding performance.
[0004] Carbon dots (CDs) have attracted a lot of research attention as a new type of material in recent decades. CDs are superior in terms of high photoluminescence (PL), easy to prepare, low toxicity, good water solubility, multifunctional surface chemistry, and good biocompatibility. Due to their excellent UV absorption capacity and chemical inertness, CDs are widely considered to be potential candidates for the preparation of highly transparent UV-shielding nanocomposites. However, commercially available carbon dots have not yet achieved full shielding in the entire UV band, and their shielding performance is poor, and their aging resistance and acid and alkali resistance are weak.
[0005] Outdoor protective materials such as anti-ultraviolet films are increasingly becoming the most widely used part. It requires the material to maintain high light performance stability under long-term ultraviolet irradiation, maintain high acid and alkali corrosion resistance in an environment with increasingly serious acid rain, and have high visible light transmittance in special applications. Currently, the organic and inorganic ultraviolet absorbers on the market have many disadvantages, such as the inability to absorb the entire ultraviolet band, low transparency, acid and alkali resistance, stability and weather resistance are not enough for long-term use, etc. They cannot become ideal ultraviolet shielding agents, and cannot be compounded with organic materials to prepare ultraviolet shielding films that can be used outdoors. Due to climate change and the increasing demand for sunscreen products, we found that the parasols on the market are all non-transparent umbrella cloths, and most of them are black on one side, which is not beautiful. Summary of the invention
[0006] The present invention aims to solve at least one of the technical problems existing in the prior art. To this end, the first aspect of the present invention is to provide a method for preparing nitrogen-doped carbon dots, wherein the carbon dots prepared by the method have broad-spectrum absorption performance in the entire ultraviolet band, high absorption efficiency, and excellent transmittance in the visible light region of 400 to 800 nm.
[0007] The second aspect of the present invention is to provide nitrogen-doped carbon dots obtained by the preparation method.
[0008] The invention also provides application of the nitrogen-doped carbon dots.
[0009] Specifically, the present invention adopts the following technical solutions:
[0010] The first aspect of the present invention is to propose a method for preparing nitrogen-doped carbon dots, comprising the following steps: mixing a carbon source and a nitrogen source, performing a hydrothermal reaction, and obtaining nitrogen-doped carbon dots; the carbon source comprises an organic carboxylic acid compound, and the nitrogen source comprises a 5-12-membered N-containing heterocyclic compound.
[0011] Nitrogen has 5 valence electrons and its atomic size is comparable to that of carbon, so nitrogen doping is the most commonly used method to improve the performance of CDs. The carbon source of the present invention contains carboxyl groups, which are beneficial to the formation of carbon cores on the one hand, and these carboxyl structures can react with amino groups and -NH structures in the nitrogen source on the other hand to generate O=CN- structures that are beneficial to shielding in the UV-A and UV-B regions. At the same time, a 5-12-membered N-containing heterocyclic compound is used as a nitrogen source, and there are a large number of CNC structures with such nitrogen sources, which is beneficial to the embedding of N elements into the carbon grid structure of the carbon core on the one hand, and on the other hand, it is beneficial to increase the diversity of functional groups on the surface of carbon dots, which is beneficial to its absorption capacity in the ultraviolet band. Therefore, the present invention prepares nitrogen-doped carbon dots by using carbon sources and nitrogen sources of specific structures, so that the nitrogen-doped carbon dots have excellent ultraviolet absorption characteristics, have broad-spectrum absorption performance in the entire ultraviolet band, have high absorption efficiency, and have excellent transmittance in the visible light region of 400-800nm.
[0012] In some embodiments of the present invention, the 5- to 12-membered N-containing heterocyclic compound has any one or more structures of the following formula 1 and formula 2:
[0013]
[0014] Among them, R 11 and R 13 are independently selected from H or C 1~6 Alkyl, R 12 Selected from =O or =S, R 14 and R 15 are independently selected from H, C 1~6 Alkyl, =O or =S; R 21 and R 22 are independently selected from H, -NH2, -NO2, -CN, -OH, -SH, -SO3H, C 1~6 Carboxyl or -CHO.
[0015] In the present invention, C 1~6 Alkyl refers to a straight chain or straight chain aliphatic alkane or cycloalkane containing 1 to 6 carbon atoms, such as methyl, ethyl, propyl, butyl, various configurations of pentyl and hexyl, and any one of cyclopropyl, cyclopentyl and cyclobutyl. 1~6 The alkyl group is preferably C 1~3 alkyl.
[0016] Similarly, C 1~6 The carboxyl group is a straight chain or straight chain aliphatic alkane carboxyl or cyclic carboxyl group containing 1 to 6 carbon atoms, such as methyl, ethyl, propyl, butyl, and various configurations of pentyl and hexyl, as well as any one of cyclopropyl, cyclopentyl and cyclobutyl. 1~6 The alkyl group is preferably C 1~3alkyl.
[0017] In some embodiments of the present invention, R 15 Selected from =O or =S.
[0018] In some examples of the present invention, the nitrogen source includes any one or more of formylhydantoin, 3-aminoquinoline and hydantoin.
[0019] In some examples of the present invention, the carbon source includes any one or more of a dicarboxylic acid compound, a tricarboxylic acid compound and a tetracarboxylic acid compound.
[0020] In some examples of the present invention, the tricarboxylic acid compound includes any one or both of malic acid and terephthalic acid.
[0021] In some examples of the present invention, the tricarboxylic acid compound includes any one or two of citric acid and trimesic acid.
[0022] In some examples of the present invention, the tetracarboxylic acid compound includes any one or both of ethylenediaminetetraacetic acid (EDTA) and pyromellitic acid.
[0023] In some examples of the present invention, the carbon source includes any one or more of citric acid, ethylenediaminetetraacetic acid (EDTA), and pyromellitic acid.
[0024] In some examples of the present invention, the molar ratio of the carbon source to the nitrogen source is 1:3-10, preferably 1:4-6, including but not limited to 1:3, 1:4, 1:5, 1:6, 1:7, 1:8, 1:9, 1:10.
[0025] In some examples of the present invention, in the hydrothermal reaction system, the concentration of the carbon source is 0.005-0.1M, preferably 0.005-0.05M, more preferably 0.008-0.02M, including but not limited to 0.005, 0.007, 0.009, 0.01, 0.03, 0.05, 0.07, 0.09, 0.1M.
[0026] The hydrothermal reaction system described in the present invention refers to a mixed solution formed by mixing a carbon source, a nitrogen source and water.
[0027] In some examples of the present invention, the temperature of the hydrothermal reaction is 160-200°C, including but not limited to 160, 170, 180, 190, 200°C.
[0028] In some examples of the present invention, the hydrothermal reaction time is 6 to 10 hours, including but not limited to 6, 7, 8, 9, 10 hours.
[0029] In some examples of the present invention, during the hydrothermal reaction, the volume ratio of the mixed solution formed by mixing the carbon source, the nitrogen source and water to the volume ratio of the container used for the hydrothermal reaction is 1:1.5-10, preferably 1:1.5-5, more preferably 1:1.5-3, including but not limited to 1:1.5, 1:2, 1:3, 1:4, 1:5, 1:6, 1:7, 1:8, 1:9, 1:10 and the like.
[0030] In some embodiments of the present invention, after the hydrothermal reaction is completed, the step of purifying the product is also included. The purification step can adopt the common standing, centrifugation, dialysis, drying and other operations in the art. Preferably, after the hydrothermal reaction is completed, the following steps are also included: solid-liquid separation of the product obtained by the hydrothermal reaction, and dialysis of the separated liquid. The solid-liquid separation method can adopt one or two of the operations of standing, centrifugation, etc.; in the dialysis step, the product with a molecular weight greater than or equal to 1000Da is retained to obtain nitrogen-doped carbon dots. Drying is performed after dialysis, and the drying temperature can be set to 80-100°C. The drying time can be determined according to the actual degree of drying, for example, 20-100h, preferably 30-80h, and preferably 64-80h.
[0031] The second aspect of the present invention is to provide nitrogen-doped carbon dots obtained by the above preparation method.
[0032] The third aspect of the present invention is to provide the use of the nitrogen-doped carbon dots in the preparation of ultraviolet absorbing products.
[0033] A fourth aspect of the present invention is to provide a polymer film, wherein the polymer film comprises the nitrogen-doped carbon dots and a polymer material.
[0034] In some examples of the present invention, the polymer material includes any one or more of polyvinyl alcohol (PVA), polymethyl methacrylate (PMMA), and polyvinylidene fluoride (PVDF). The polymer material can be transparent or opaque. When a transparent polymer material and the nitrogen-doped carbon dots are used together to form a film, the nitrogen-doped carbon dots will not affect the light transmittance of the film, and the obtained film still has good light transmittance.
[0035] In some examples of the present invention, the content of the nitrogen-doped carbon dots in the polymer film is 0.1wt% to 2wt%, preferably 0.1wt% to 1wt%, and more preferably 0.1wt% to 0.5wt%, including but not limited to 0.1wt%, 0.3wt%, 0.5wt%, 0.7wt%, 0.9wt%, 1wt%, 1.3wt%, 1.5wt%, 2wt%, etc.
[0036] The fifth aspect of the present invention is to provide a sunshade product, which contains the nitrogen-doped carbon dots or the polymer film. The sunshade product can be any one or more of a transparent or opaque parasol cloth, a sunshade garment, and a sunshade film for building materials (such as a window glass film).
[0037] Compared with the prior art, the present invention has the following beneficial effects:
[0038] The present invention adopts a carboxyl-containing carbon source to prepare nitrogen-doped carbon dots, which is beneficial to the formation of carbon cores on the one hand, and these carboxyl structures can react with amino and -NH structures in the nitrogen source on the other hand to generate O=CN- structures that are beneficial to shielding in the UV-A and UV-B regions. At the same time, a 5-12-membered N-containing heterocyclic compound is used as a nitrogen source, and there are a large number of CNC structures with such nitrogen sources, which is beneficial to embedding the N element into the carbon grid structure of the carbon core on the one hand, and on the other hand, it is beneficial to improve the diversity of functional groups on the surface of the carbon dots, which is beneficial to its absorption capacity in the ultraviolet band. Therefore, the present invention prepares nitrogen-doped carbon dots by adopting carbon sources and nitrogen sources with specific structures, so that the nitrogen-doped carbon dots have excellent ultraviolet absorption characteristics, have broad-spectrum absorption performance in the entire ultraviolet band, have an absorption efficiency of more than 99%, and have excellent transmittance in the visible light region of 400-800nm.
[0039] In addition, the nitrogen-doped carbon dots prepared by the present invention have excellent light aging resistance and acid resistance. Since the reaction conditions are high temperature, the nitrogen-doped carbon dots will not be affected even in high temperature outdoors and have good high temperature resistance.
[0040] Therefore, the nitrogen-doped carbon dots prepared by the present invention can be used to prepare ultraviolet absorption products, sunshade products, etc., for example, made into polymer films, made into parasol cloths, etc., and have very good industrial application prospects. BRIEF DESCRIPTION OF THE DRAWINGS
[0041] Figure 1 This is the UV absorption spectrum of 1-CDs.
[0042] Figure 2 This is the UV absorption spectrum of 2-CDs.
[0043] Figure 3 This is the UV absorption spectrum of 3-CDs.
[0044] Figure 4 This is the UV absorption spectrum of 4-CDs.
[0045] Figure 5 This is the UV absorption spectrum of 5-CDs.
[0046] Figure 6 This is the UV absorption spectrum of 6-CDs.
[0047] Figure 7 This is the UV absorption spectrum of 7-CDs.
[0048] Figure 8 Light transmittance spectra of CDs / PVA films at different CDs doping levels.
[0049] Fig. 9 Actual pictures of CDs / PVA films at different CDs dosages.
[0050] Fig.10 This is the light transmission spectrum of the umbrella cloth sandwich CDs / PVA film. DETAILED DESCRIPTION
[0051] The technical scheme of the present invention is further described below in conjunction with specific examples. The raw materials used in the following examples, unless otherwise specified, can all be obtained from conventional commercial sources; the processes used, unless otherwise specified, all adopt conventional processes in the art.
[0052] Example 1
[0053] This embodiment provides a nitrogen-doped carbon dots CDs, and the preparation method thereof comprises the following steps:
[0054] A mixed solution containing 0.01 M citric acid CA and 0.05 M formyl hydantoin was prepared using 25 mL of H2O, and the mixed solution was placed in a 50 mL polytetrafluoroethylene reactor, and then placed in a vacuum oven at 180°C for reaction for 8 h.
[0055] After the reaction, the colorless solution turned into a yellow-brown solution, indicating the successful synthesis of carbon dots. The obtained product was placed in a centrifuge and centrifuged at 8000 rpm for five minutes to remove large particles. The supernatant after centrifugation was fully dialyzed for 72 hours using a dialysis bag with a molecular weight of 1000 Da. The dialyzed product was placed in a vacuum drying oven and kept at 90°C for 72 hours to obtain a dry product, which was labeled as 1-CDs.
[0056] After calculation, the yield of 1-CDs was 34%.
[0057] 1-CDs was prepared into a 1.5 μL / mL aqueous solution and the UV absorption spectrum of 1-CDs was obtained. Figure 1 As shown, the results show that 1-CDs has good absorption performance in the entire ultraviolet band, the absorption efficiency in the ultraviolet band can reach more than 99%, and the transmittance in the visible light region of 400-800nm is excellent, that is, it does not affect the transmittance of visible light.
[0058] After irradiating 1-CDs with 365nm UV lamp for 180 hours, it was found that its UV shielding performance (absorption efficiency in the UV band) was only reduced by 2%, and its light aging resistance was very excellent.
[0059] After adjusting the acidity and alkalinity of CDs aqueous solution many times, its UV shielding performance remains good, indicating that its carbon core and surface structure are very stable.
[0060] Example 2
[0061] This embodiment provides a nitrogen-doped carbon dots CDs, and the preparation method thereof is different from that of embodiment 1 in that formylhydantoin is replaced with 3-aminoquinoline of the same molar concentration, and specifically comprises the following steps:
[0062] A mixed solution containing 0.01 M CA and 0.05 M 3-aminoquinoline was prepared using 25 mL of H2O, and the mixed solution was placed in a 50 mL polytetrafluoroethylene reactor. The entire device was placed in a vacuum oven and reacted at 180°C for 8 h.
[0063] After the reaction, the colorless solution turned into a yellow-brown solution, indicating the successful synthesis of carbon dots. The obtained product was placed in a centrifuge and centrifuged at 8000 rpm for five minutes to remove large particles. The supernatant after centrifugation was fully dialyzed for 72 hours using a dialysis bag with a molecular weight of 1000 Da. The dialyzed product was placed in a vacuum drying oven and kept at 90°C for 72 hours to obtain a dry product, namely nitrogen-doped carbon dots, labeled as 2-CDs.
[0064] After calculation, the yield of 2-CDs was 31%.
[0065] The UV absorption spectrum of 2-CDs is as follows Figure 2 As shown, the results show that 2-CDs has good absorption performance in the entire ultraviolet band, the absorption efficiency in the ultraviolet band can reach more than 99%, and the transmittance in the visible light region of 400-800nm is excellent.
[0066] After irradiating 2-CDs with 365nm UV lamp for 180 hours, it was found that its absorption efficiency in the UV band decreased by less than 5%, and its light aging resistance was very excellent.
[0067] Example 3
[0068] This embodiment provides a nitrogen-doped carbon dots CDs, and the preparation method thereof is different from that of embodiment 1 in that formylhydantoin is replaced with hydantoin of the same molar concentration, and specifically comprises the following steps:
[0069] A mixed solution containing 0.01 M CA and 0.05 M hydantoin was prepared in 25 mL of H2O, and the mixed solution was placed in a 50 mL polytetrafluoroethylene reactor. The entire device was placed in a vacuum oven and reacted at 180°C for 8 h.
[0070] After the reaction, the colorless solution turned into a yellow-brown solution, indicating the successful synthesis of carbon dots. The obtained product was placed in a centrifuge and centrifuged at 8000 rpm for five minutes to remove large particles. The supernatant after centrifugation was fully dialyzed for 72 hours using a dialysis bag with a molecular weight of 1000 Da. The dialyzed product was placed in a vacuum drying oven and kept at 90°C for 72 hours to obtain a dry product, which was labeled as 3-CDs.
[0071] The yield of 3-CDs was calculated to be 26%.
[0072] The UV absorption spectrum of 3-CDs is as follows Figure 3 As shown, the results show that 3-CDs has good absorption performance in the entire ultraviolet band, the absorption efficiency in the ultraviolet band can reach more than 99%, and the transmittance in the visible light region of 400-800nm is excellent.
[0073] After irradiating 3-CDs with 365nm UV lamp for 180 hours, it was found that its absorption efficiency in the UV band decreased by less than 5%, and its light aging resistance was very excellent.
[0074] Example 4
[0075] This embodiment provides a nitrogen-doped carbon dots CDs, and the preparation method thereof is different from that of embodiment 2 in that citric acid CA is replaced with EDTA of the same molar concentration, and specifically comprises the following steps:
[0076] A mixed solution containing 0.01 M EDTA and 0.05 M 3-aminoquinoline was prepared in 25 mL of H2O, and the mixed solution was placed in a 50 mL polytetrafluoroethylene reactor. The entire device was placed in a vacuum oven and reacted at 180°C for 8 hours.
[0077] After the reaction, the colorless solution turned into a yellow-brown solution, indicating the successful synthesis of carbon dots. The obtained product was placed in a centrifuge and centrifuged at 8000 rpm for five minutes to remove large particles. The supernatant after centrifugation was fully dialyzed for 72 hours using a dialysis bag with a molecular weight of 1000 Da. The dialyzed product was placed in a vacuum drying oven and kept at 90°C for 72 hours to obtain a dry product, which was labeled as 4-CDs.
[0078] The yield of 4-CDs was calculated to be 28%.
[0079] The UV absorption spectrum of 4-CDs is as follows Figure 4As shown, the results show that 4-CDs has good absorption performance in the entire ultraviolet band, the absorption efficiency in the ultraviolet band can reach more than 99%, and the transmittance in the visible light region of 400-800nm is excellent.
[0080] After irradiating 4-CDs with 365nm UV lamp for 180 hours, it was found that its absorption efficiency in the UV band decreased by less than 5%, and its light aging resistance was very excellent.
[0081] Example 5
[0082] This embodiment provides a nitrogen-doped carbon dots CDs, and the preparation method thereof is different from that of embodiment 2 in that citric acid CA is replaced with pyromellitic acid of the same molar concentration, and specifically comprises the following steps:
[0083] A mixed solution containing 0.01 M pyromellitic acid and 0.05 M 3-aminoquinoline was prepared in 25 mL of H2O, and the mixed solution was placed in a 50 mL polytetrafluoroethylene reactor. The entire device was placed in a vacuum oven and reacted at 180°C for 8 hours.
[0084] After the reaction, the colorless solution turned into a yellow-brown solution, indicating the successful synthesis of carbon dots. The obtained product was placed in a centrifuge and centrifuged at 8000 rpm for five minutes to remove large particles. The supernatant after centrifugation was fully dialyzed for 72 hours using a dialysis bag with a molecular weight of 1000 Da. The dialyzed product was placed in a vacuum drying oven and kept at 90°C for 72 hours to obtain a dry product, which was labeled as 5-CDs.
[0085] The yield of 5-CDs was calculated to be 24%.
[0086] The UV absorption spectrum of 5-CDs is as follows Figure 5 As shown, the results show that 5-CDs has good absorption performance in the entire ultraviolet band, the absorption efficiency in the ultraviolet band can reach more than 99%, and the transmittance in the visible light region of 400-800nm is excellent.
[0087] After irradiating 5-CDs with 365nm UV lamp for 180 hours, it was found that its absorption efficiency in the UV band decreased by less than 5%, and its light aging resistance was very excellent.
[0088] Comparative Example 1
[0089] This comparative example provides a nitrogen-doped carbon dots CDs, and the preparation method thereof is different from that of Example 1 in that formylhydantoin is replaced with ethylenediamine EDA of the same molar concentration, and specifically comprises the following steps:
[0090] A mixed solution containing 0.01 M CA and 0.05 M EDA was prepared in 25 mL of H2O, and the mixed solution was placed in a 50 mL polytetrafluoroethylene reactor. The entire device was placed in a vacuum oven and reacted at 180°C for 8 h.
[0091] The obtained product was placed in a centrifuge and centrifuged at 8000 rpm for five minutes to remove large particles. The supernatant after centrifugation was fully dialyzed for 72 hours using a dialysis bag with a molecular weight of 1000 Da. The dialyzed product was placed in a vacuum drying oven and dried at 90° C. for 72 hours to obtain a dry product, which was labeled as 6-CDs.
[0092] The yield of 6-CDs was calculated to be 18%.
[0093] The UV absorption spectrum of 6-CDs is as follows Figure 6 As shown, the results show that 6-CDs only has certain ultraviolet absorption performance in the 250-300nm band, but cannot absorb other ultraviolet bands, indicating that the change of nitrogen source will significantly affect the ultraviolet absorption performance of carbon dots, and nitrogen-doped carbon dots with full ultraviolet band absorption performance cannot be obtained using EDA as the nitrogen source.
[0094] At the same time, from Figure 6 It can be seen that the excitation wavelength of 6-CDs is about 350nm, and it emits blue light of about 450nm under 350nm light excitation.
[0095] Comparative Example 2
[0096] This comparative example provides a nitrogen-doped carbon dots CDs, and the preparation method thereof is different from that of Example 1 in that formylhydantoin is replaced with urea of the same molar concentration, and specifically comprises the following steps:
[0097] A mixed solution containing 0.01 M CA and 0.05 M urea was prepared in 25 mL of H2O, and the mixed solution was placed in a 50 mL polytetrafluoroethylene reactor. The entire device was placed in a vacuum oven and reacted at 180°C for 8 h.
[0098] The obtained product was placed in a centrifuge and centrifuged at 8000 rpm for five minutes to remove large particles. The supernatant after centrifugation was fully dialyzed for 72 hours using a dialysis bag with a molecular weight of 1000 Da. The dialyzed product was placed in a vacuum drying oven and dried at 90° C. for 72 hours to obtain a dry product, which was labeled as 7-CDs.
[0099] The yield of 7-CDs was calculated to be 15%.
[0100] The UV absorption spectrum of 7-CDs is as follows Figure 7 The results show that, similar to 6-CDs, 7-CDs cannot absorb the entire UV band.
[0101] Example 6
[0102] This embodiment provides a carbon dot / PVD composite film, and the preparation method thereof comprises the following steps:
[0103] Take 0.7g PVA and 15mL deionized water in a beaker, heat and stir for 1.5h, and after it is completely dissolved, add 0wt%, 0.1wt%, 0.2wt%, 0.3wt%, 0.4wt%, 0.5wt% 1-CDs respectively, and stir at room temperature for 10min until 1-CDs are evenly dispersed in the PVA aqueous solution. Pour the mixed aqueous solution into a glass petri dish, put it in a 70℃ oven and dry it overnight, and then tear it off with tweezers to obtain a carbon dot / PVD composite film, that is, CDs / PVA film.
[0104] A CDs / PVA film with a 1-CDs content of 0.5 wt% was superimposed on a commercial umbrella cloth (the CDs / PVA film was sandwiched between two layers of transparent umbrella cloth) to obtain an umbrella cloth sandwiched CDs / PVA film.
[0105] The light transmission spectra and physical images of CDs / PVA films with different CDs doping levels are shown in Figure 2. Figure 8 and Fig. 9 As shown, Figure 8 The amount of nitrogen-doped carbon dots increases gradually in the direction of the arrow. Fig.10 As shown, Fig.10 The curves in the direction of the arrows are umbrella cloth (without any CDs / PVA film), 0.5wt% CDs / PVA film and umbrella cloth sandwiched with 0.5wt% CDs / PVA film.
[0106] from Figure 8 , 9It can be found from Figures 10 that, whether it is CDs / PVA film or the product after CDs / PVA film is superimposed with commercial umbrella cloth, its shielding performance in the entire ultraviolet band is very excellent, and it has good transmittance in the visible light region. For six gradient CDs / PVA films, that is, the CDs content is 0wt%, 0.1wt%, 0.2wt%, 0.3wt%, 0.4wt%, 0.5wt%, among which the pure PVA film has almost no ultraviolet absorption performance, which shows that the absorption performance of the composite product is almost entirely from nitrogen-doped carbon dots, and can most realistically show the absorption characteristics of the CDs. The sample with only 0.2wt% CDs content can achieve a transmittance of 0% in the entire ultraviolet region. As the content of CDs doped in the PVA film increases, the wavelength when the transmittance drops to 0 red shifts from 390nm to 430nm, and the product changes from simply absorbing ultraviolet light to absorbing blue light of a certain wavelength. This characteristic is very valuable for application.
[0107] Since PVA film is susceptible to moisture, it is not ideal to use it as a material for umbrella cloth alone. In view of the fact that most parasol materials on the market are opaque and mostly black and unsightly, this embodiment sandwiches PVA film as an interlayer between two layers of transparent umbrella cloth. It is found that pure umbrella cloth has almost no UV absorption ability like pure PVA film, and its transmittance in the visible light region is similar to that of composite PVA film, which will not have much effect on the transparency of the superimposed sample. As expected, the transmittance curve of the double-layer umbrella cloth sandwiched with 0.5wt% CDs / PVA film is almost overlapped with the curve of 0.5wt% CDs / PVA film, and is only slightly inferior in transparency in part of the visible light region. The overall effect is still very impressive.
[0108] The above embodiments are preferred implementation modes of the present invention, but the implementation modes of the present invention are not limited to the above embodiments. Any other changes, modifications, substitutions, combinations, and simplifications that do not deviate from the spirit and principles of the present invention should be equivalent replacement methods and are included in the protection scope of the present invention.
Claims
1. A method for preparing nitrogen-doped carbon dots, characterized in that: The method comprises the following steps: mixing a carbon source and a nitrogen source, and performing a hydrothermal reaction to obtain nitrogen-doped carbon dots; the carbon source comprises an organic carboxylic acid compound, and the nitrogen source comprises a 5-12-membered N-containing heterocyclic compound; The 5- to 12-membered N-containing heterocyclic compound has any one or more structures of the following formula 1 and formula 2: Among them, R 11 and R 13 are independently selected from H or C 1~6 Alkyl, R 12 =O, R 14 and R 15 are independently selected from H or =O; R 21 and R 22 are independently selected from H or -NH2, and R 21 and R 22 Not the same.
2. The preparation method according to claim 1, characterized in that: The nitrogen source includes any one or more of formylhydantoin, 3-aminoquinoline and hydantoin.
3. The preparation method according to claim 1, characterized in that: The carbon source includes any one or more of a dicarboxylic acid compound, a tricarboxylic acid compound and a tetracarboxylic acid compound.
4. The preparation method according to claim 1, characterized in that: The molar ratio of the carbon source to the nitrogen source is 1:3-10.
5. Nitrogen-doped carbon dots obtained by the preparation method according to any one of claims 1 to 4.
6. Use of the nitrogen-doped carbon dots according to claim 5 in the preparation of ultraviolet absorbing products.
7. A polymer film, characterized in that: The polymer film comprises the nitrogen-doped carbon dots as claimed in claim 5 and a polymer material.
8. A sunshade product, characterized in that: The sunshade product contains the nitrogen-doped carbon dots described in claim 5 or the polymer film described in claim 7.
Citation Information
Patent Citations
Carbon quantum dot precursor composition, carbon quantum dot and preparation method thereof
CN112978709A